Efeito do óleo essencial de tangerina 'Fremont' no controle de Lactobacillus fermentum na fermentação alcoólica - Varano, Amanda (2021)
Bacteria of Lactobacillus genus are one of the most frequent biological contaminants in the ethanol production. Contamination control has been performed with antibiotics and acid treatment, although be effective, these techniques have limitations, which promotes the search for other antimicrobials. In this work, the antimicrobial activity of essential oil (EO) from ‘Fremont’ IAC 543 mandarin (cultivated at Poncirus trifoliata rootstock) on Lactobacillus fermentum, a contaminant bacterium from the ethanolic fermentation process, and Saccharomyces cerevisiae PE-2, an industrial yeast, have been evaluated. The OE was obtained by hydrodistillation and the following effects were studied: EO on L. fermentum in proliferative conditions (microdilution testes and disk diffusion); pH in addition with EO to control L. fermentum in non-proliferative condition; EO on L. fermentum and S. cerevisiae in proliferative and non-proliferative conditions (time-kill); EO concentration in non-proliferative conditions to control L. fermentum, in order to have minimal effect on S. cerevisiae viability; EO on L. fermentum and S. cerevisiae in co-culture; and EO application in cell treatment of fermentative cycles. In disk-diffusion assay, antibacterial activity was observed only with EO without dilution. Although, in microdilution test in proliferative conditions, when EO concentration was increased from 0.05% to 12.8% v/v, which has resulted in a decrease of maximum growth specific rate and a longer lag period, there was no inhibition of bacterial growing. In non-proliferative conditions (water), 0.2% v/v EO has resulted in a decrease of four logarithmic cycles on L. fermentum, the same effect of acid treatment in 2 hours. In time-kill tests, all the bacterial viability was lost and there was a decrease of one logarithmic cycle on S. cerevisiae after 1.5 hour with 0.2% v/v EO in water. When it was used with 3 mg/L of monensin antibiotic, the overall loss of bacteria viability has occurred after 4.5 hours, however in cultivation medium with EO, it was after 6 hours. The efficiency of EO on L. fermentum was maintained and the effect was lower for S. cerevisiae with the reduction of EO concentration from 0.2% to 0.05% v/v. At the last concentration, EO effect was lower for both microorganisms in co-culture. In sugar cane juice and adding EO to the cell treatments at three fermentative cycles, it was observed a decrease of 1.5 log cycles for yeast and bacterium, a lower ethanol production, increase in residual sugar concentration and pH. The results obtained has invalidated the application of the EO on fermentative process to control L. fermentum, nevertheless, the satisfactory antibacterial action revealed in pure cultivation stimulates further studies to discover new alternatives for EO to replace sulfuric acid in the cell treatment during fermentation process for bioethanol production.